2018
DOI: 10.5935/0004-2749.20180044
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestations of psoriasis

Abstract: Patients with psoriasis should undergo regular eye exams, regardless of risk factors, to monitor for the progression of symptomatic or asymptomatic ocular manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 0 publications
2
31
0
7
Order By: Relevance
“…The most common clinical ocular change associated with psoriasis is keratoconjunctivitis sicca (dry eye syndrome), which is present in 18.75% of patients, and blepharitis (2,12,13). Other changes include conjunctivitis, uveitis, punctate keratitis, pinguecula, cataracts, glaucoma, corneal abscesses, pterygium, or abnormalities of retinal vascularization (5,14).…”
Section: Ophthalmological Changesmentioning
confidence: 99%
See 3 more Smart Citations
“…The most common clinical ocular change associated with psoriasis is keratoconjunctivitis sicca (dry eye syndrome), which is present in 18.75% of patients, and blepharitis (2,12,13). Other changes include conjunctivitis, uveitis, punctate keratitis, pinguecula, cataracts, glaucoma, corneal abscesses, pterygium, or abnormalities of retinal vascularization (5,14).…”
Section: Ophthalmological Changesmentioning
confidence: 99%
“…Several studies on patients with psoriasis have demonstrated an association between Psoriasis Area and Severity Index (PASI) scores and the presence of ocular manifestations. Patients with blepharitis tend to have low PASI scores, whilst patients with keratitis have moderate-to-severe PASI scores (2,14). Paradoxically, a study performed in 2013 on 100 patients with psoriasis concluded that there is no significant association between severe cases of psoriasis and eye lesions; therefore, all patients should be evaluated ophthalmologically to establish an accurate diagnosis (12).…”
Section: Ophthalmological Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…As in most systemic, inflammatory, chronic diseases, ocular manifestations can occur (35). The incidence of ocular involvement in psoriasis largely varies in the literature between 12 and 58% (36,37) and even up to 81.4% in more recent studies (38). The eyelid manifestations include blepharitis, which is the most frequent one, together with erythema, psoriatic plaques, and edema leading to eyelid abnormalities such as ectropion, trichiasis, and madarosis.…”
Section: Comorbiditiesmentioning
confidence: 99%